ECOLOGICAL VALUE, CULTIVATION, UTILIZATION AND COMMERCIALIZATION OF ALOE VERA IN GREECE - A.D. Solomou1; R. Germani; M. Georgakopoulou (Journal of Animal and Plant Sciences, 2020)
Aloe vera seems to have an essential role over millennia in several cultures, as well as in Greek. Νowadays it is a fact that Greece, because of the economic crisis, focused on the cultivation of alternative plants including Aloe. This cultivation attracts the farmers’ interest both for its good adaptability to the local climate and for its beneficial properties. According to the literature, they can harvest 7,000 kg of leaves containing about 70-80% gel per acre. Also, it is noteworthy that the main purpose of the cultivation of this species, is the leaves’ processing in order to obtain its beneficial properties for skin, health, weight loss etc. In addition, as far as the domestic commercialization and market demand of Aloe vera are concerned, it is observed that they are still in an embryonic stage, and are in need of enrichment with direct supply chains with the pharmaceutical and cosmetic industries that will supply with Aloe’s gel their production lines. The present review focuses on the current state of the Aloe’s cultivation, utilization and commercialization in Greece, so it can be used as a baseline information for further research.
Keywords: Aloe vera; cultivation; ecological value; utilization; SWOT analysis; sustainability; Greece